2009
DOI: 10.1017/s1138741600001529
|View full text |Cite
|
Sign up to set email alerts
|

Parental Influences on Students' Self-Concept, Task Value Beliefs, and Achievement in Science

Abstract: The aim of this study was twofold: firstly, to investigate the grade level (elementary and middle school) and gender effect on students' motivation in science (perceived academic science self-concept and task value) and perceived family involvement, and secondly to examine the relationship among family environment variables (fathers' educational level, mothers' educational level, and perceived family involvement), motivation, gender and science achievement in elementary and middle schools. Multivariate Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 28 publications
(35 reference statements)
2
49
0
5
Order By: Relevance
“…It consisted of 6 items and these items were scored on 5 point-Likert type scales ranging from completely agree to completely disagree. Reliability coefficient of data of this scale was .83 which was higher to result of study (α = .71) of Senler and Sungur (2009). Moreover, confirmatory factor analysis showed that it have good fit (χ 2 /df = 3.12 TFI = .97, CFI = .95 and RMSEA = .05).…”
Section: The Academic Interest Questionnaire (Aiq)mentioning
confidence: 52%
See 2 more Smart Citations
“…It consisted of 6 items and these items were scored on 5 point-Likert type scales ranging from completely agree to completely disagree. Reliability coefficient of data of this scale was .83 which was higher to result of study (α = .71) of Senler and Sungur (2009). Moreover, confirmatory factor analysis showed that it have good fit (χ 2 /df = 3.12 TFI = .97, CFI = .95 and RMSEA = .05).…”
Section: The Academic Interest Questionnaire (Aiq)mentioning
confidence: 52%
“…This result may be caused by Turkish educational system. Senler and Sungur (2009) declared that Turkish students are educated competitive and examination oriented. Especially, after they graduate high school, they take highly competitive examination to enter university.…”
Section: Discussion and Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Çalışma kapsamında sınıf düzeyi ile motivasyon arasındaki ilişki incelendiğinde, sınıf düzeyi arttıkça motivasyon düzeyinin azaldığı görülmüştür. Motivasyon düzeyi ile sınıf düzeyi ilişkisine yönelik alanyazın incelendiğinde (Lepper, Corpus ve Iyengar, 2005;Güngören, Şenler ve Sungur, 2007;Aluçdibi ve Ekici, 2007;Şenler ve Sungur, 2009;Şen ve Yılmaz, 2014) sınıf düzeyi arttıkça motivasyon düzeyinin azaldığına yönelik sonuçlar bulunmuştur. İncelenen çalışmaların sonuçları bu çalışmadaki bulguyu destekler niteliktedir.…”
Section: Discussionunclassified
“…Students' academic achievement is not only necessarily formed by the classroom climate and the elementary school students are more likely to need the role of parents in their school [11]. Parents play a role in shaping student academic achievement.…”
Section: Introductionmentioning
confidence: 99%